2000
DOI: 10.1016/s0044-8486(99)00319-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the black-lip pearl oyster, Pinctada margaritifera, in suspended culture under hydrobiological conditions of Takapoto lagoon (French Polynesia)

Abstract: Growth of the black-lip pearl oyster, Pinctada margaritifera var. cumingi, was studied for an annual cycle, from March 1997 to April 1998, in the lagoon of Takapoto atoll (Tuamotu archipelago, French Polynesia). Growth in shell and in tissue were measured every 15 days on three successive age groups of cultivated pearl oysters. At the same time, hydrobiological parameters (temperature, salinity, oxygen concentration, suspended particulate matter), known to have influence on bivalve growth, were followed each w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
4
40
0
1
Order By: Relevance
“…Abraham et al (2007) obtained a much less 'R 2 -0.60-0.78', value for this species from different Islands of the Andaman and Nicobar, for a length range of 40-133 mm. Our results concerning total Wt and ShH relationship were similar to those of Alagarswami (1983) from Andaman Islands and Pouvreau et al (2000c) for farmed oysters in French Polynesia : R 2 = 0.96 and 0.97 respectively.…”
Section: Length-weight Relationshipsupporting
confidence: 88%
“…Abraham et al (2007) obtained a much less 'R 2 -0.60-0.78', value for this species from different Islands of the Andaman and Nicobar, for a length range of 40-133 mm. Our results concerning total Wt and ShH relationship were similar to those of Alagarswami (1983) from Andaman Islands and Pouvreau et al (2000c) for farmed oysters in French Polynesia : R 2 = 0.96 and 0.97 respectively.…”
Section: Length-weight Relationshipsupporting
confidence: 88%
“…The study by Pereira et al (2003) showed that the model of Von Bertalanffy was best suited for the growth data of C. brasiliana. This and the logistic model were suited for the growth data of Pinctada margaritifera (Pouvreau et al, 2000); whereas the Von Bertalanffy model described the growth in length; and the logistic model was the best fit for shell length and dry flesh weight. Yukihira et al (2006) reported that the Von Bertalanffy model ignored the slow growth of oysters in the early life stages but presented a good fit (R 2 = 0.95-0.97) for the growth of P. maxima and P. margaritifera.…”
Section: Assessedmentioning
confidence: 99%
“…The palp, visceral sac and asymmetry of pedo-byssal retractor muscle are similar to the previously described for other Pinctada species (THIELE, 1886;FOUGEROUSE-TSING and HERBAUT, 1994;TËMKIN, 2006;FOUGEROUSE et al, 2008;MAMANGKEY, 2009). The gonads follow the same pattern for the genus (BUESTEL and POUVREAU, 2000;POUVREAU et al, 2000;YUKIHIRA et al, 2006). The extrinsic muscular system is composed of the adductor muscle, with origin area occupying about 1/8 of mantle surface (Figures 8, 9).…”
Section: Methodsmentioning
confidence: 66%